Phylogeny and biogeography of the genus Pelinoides Cresson (Diptera-Ephydridae) - de Grosso, Mercedes Lizarralde; Szumik, Claudia (Zootaxa, 2007)
A phylogenetic analysis of the 21 species of genus Pelinoides using 44 discrete morphological characters is presented. From the previous proposed three groups, pallipes, sulcatus and cyclocerus, the first is recovered. The sulcatus group appears as paraphyletic in terms of cyclocerus. Pelinoides is present in the Neotropical and Andean Regions and in the Transitional South American Zone. Four areas of maximum endemicity were found. Eleven vicariant events are described and discussed, using the areas of endemisms and biogeographic provinces where Pelinoides occurs.